The PI3K/Akt1-FoxO1 Translocation Pathway Mediates EXf Effects on NIT-1 Cell Survival - Hou, Guo-jiang; Li, Cai-na; Huan, Yi; Liu, Shuai-nan; Liu, Quan; Liu, Min-zhi; Shen, Zhu-fang (Experimental and Clinical Endocrinology & Diabetes, 2017)
EXf, a glucagon-like peptide 1 (GLP-1) receptor agonist, stimulates β-cell proliferation and reduces apoptosis in diabetic animal models, but the underlying mechanisms are not fully understood. We constructed a FoxO1-GFP fusion protein expression plasmid and transiently transfected it into NIT-1 cells to investigate whether FoxO1 mediates EXf effects on NIT-1 cell survival. Our results showed that EXf could increase cell viability by inhibiting apoptosis and stimulating proliferation, and it could also promote the translocation of the FoxO1-GFP fusion protein from the nucleus to the cytoplasm in NIT-1 cells. However, the above effects of EXf were suppressed by the inhibitor of PI3K. Comparative transcription analysis showed up-regulation of igf-1r, irs-2, pI3k, akt1 and pdx-1 in NIT-1 cells after EXf treatment. Moreover, the up-regulation of PI3K and phosphorylation of Akt1 upon EXf treatment was confirmed by Western blot, both phenomena were abrogated by wortmannin, an inhibitor of PI3K. In summary, FoxO1 may mediate the effects of EXf on NIT-1 cell survival by activating the PI3K/Akt1 pathway.
Keywords: EXf; GLP-1; FoxO1; NIT-1 cells; translocation